Synthesis of Novel Diarylsulfonylurea-chalcone Hybrid Molecules with Potential In Vitro Antimicrobial Activity (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: To study the antimicrobial effect of novel diarylsulfonylurea-chalcone hybrids with significant associated morbidity and mortality which is mainly due to the development of microbial resistance to the existing antimicrobial agents. Materials and Methods: The antimicrobial effect of novel diarylsulfonylurea-chalcone hybrid molecules was evaluated by agar well diffusion method against various strains of bacteria and fungi. Results: Most of the compounds showed promising antibacterial and antifungal activity. Conclusion: The results in the present study suggest that novel diarylsulfonylurea-chalcone hybrids can be used in treating diseases caused by the tested organisms.